Accept mobile: a mobile tool for the SINMETRO accept information system - Caldeira, J.M.L.P. (2011)
Increasing demand of mobile applications for on-site data acquisition pushes the development of flexible and easy to use mobile tools, with great advantages over the traditional computer-based approaches. The Accept System from SINMETRO allows data gathering for quality control, in the form of Inspection sheets. Such tool allows quality assurance by monitoring some samples of a given material, for instance milk, wine, and even maintenance management. This paper presents a mobile application in the Accept System that allows a Personal Digital Assistant (PDA) device to perform data gathering based on XML Inspection templates. Using .NET Compact Framework through C#, and database the technologies SQL Server and SQL Server CE, we developed Accept Mobile. Accept Mobile uses the Remote Data Access (RDA) mechanism to send data over to the server through a synchronization service, while also providing the needed support for disconnected operation. We prove that the mobile application is very convenient and provides enough functionality for the user to dismiss the portable computer, although the main application was never developed with mobility concerns in mind.